A Crystalline π‐Stack Containing Five Stereoisomers: Insights into Conformational Isomorphism, Chirality Inversion, and Disorder. Issue 39 (18th August 2017) - Nowak‐Król, Agnieszka; Röhr, Merle I. S.; Schmidt, David; Würthner, Frank
Abstract: An unprecedented crystal‐packing arrangement of a tetramethoxy‐bay‐substituted perylene bisimide (PBI) consists of three crystallographically independent molecules, that is, an achiral (AC ) PBI of saddle‐shaped geometry along with two pairs of propeller‐like twisted ( P )‐ and ( M )‐enantiomeric PBI frameworks. All these five conformations are observed within a single π‐stack revealing an intriguing packing sequence with an inversion of chirality from P to M viaAC . Nudged elastic band calculations for the isolated molecule show thatAC is a local minimum of the P to M interconversion path. In addition, two minor conformations were observed in the crystal, one of which resembles a transition‐state molecule. Theoretical studies of dimeric and trimeric stacks reveal that the coexistence of all these structures in the crystal lattice is aided by the strong dispersion interactions between PBI cores and perfectly interdigitated dodecyl chains which stabilize energetically higher conformations. Abstract : From hand to hand : A unique crystal‐packing arrangement of bay‐substituted perylene bisimide consists of propeller‐like twisted and achiral stereoisomers. All the conformations are assembled in a single regular π‐stack showing an inversion of chirality from P to M via an achiral molecule. Coexistence of these conformations in the crystal lattice is attributed to the strong dispersion forces.